Establishment of a controlled slow freezing-based approach for experimental clinical cryopreservation of human prepubertal testicular tissues - Doron Kabiri, M.D; Myriam Safrai, M.D; Michal Gropp, Ph.D; Guy Hidas, M.D; Talya Mordechai-Daniel, Ph.D; Karen Meir, M.D; Ariel Revel, M.D; Tal Imbar, M.D; Benjamin Reubinoff, M.D (Elsevier, 2022)
Objective: To develop an efficient, clinical-grade, freezing protocol toward experimental clinical cryopreservation of testicular tissues in prepubertal boys suffering from cancer. Design: Experimental cryopreservation of testicular tissue. Setting: University Medical Center. Patient(s): Adult patients undergoing orchiectomy for various tumors and prepubertal boys scheduled for gonadotoxic treatment. Intervention(s): None. Main Outcome Measure(s): Histopathological analysis of tissue architecture, structural integrity, and cellular morphology was performed for control and frozen-thawed cryopreserved tissues.The number of seminiferous tubules per testicular section was calculated. The survival of spermatogonial stem cells (SSCs) and Sertoli cells of the control and frozen-thawed cryopreserved tissues was analyzed by immunofluorescence staining. Result(s): Uncontrolled Slow Freezing, Controlled slow freezing, and vitrification similarly preserved the integrity of the adult testicular tissues and the survival of SSCs and Sertoli cells. Controlled slow freezing of prepubertal testicular tissues effectively preserved their architecture, the number of tubules, SSCs, and Sertoli cells. In addition, we observed SSC loss after chemotherapy in prepubertal boys, reemphasizing the importance of fertility preservation before gonadotoxic treatment. Conclusion(s): Future fertility restoration for male survivors of pediatric cancers depends on the development of an optimal prepubertal testicular tissue cryopreservation method. Our findings demonstrate the effectiveness of controlled slow freezing for cryopreservation of human prepubertal testicular tissues and may contribute to more effective banking of these tissues and potential fertility restoration. Clinical Trial Registration Number: NIH research clinical trials number: NCT02529826.